2016
DOI: 10.1353/jef.2016.0006
|View full text |Cite
|
Sign up to set email alerts
|

Does Performance-Based Funding Affect Colleges’ Financial Priorities?

Abstract: State-level performance-based funding (PBF) policies are an increasingly common way to allocate funds to public colleges and universities. While a growing body of research has examined whether these policies are effective in improving student outcomes, little is known about how colleges respond to PBF policies. In this paper, we examine whether two-year and four-year colleges subject to PBF change their patterns and allocations of revenues, expenditures, and financial aid. We find limited evidence that college… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 21 publications
2
69
2
Order By: Relevance
“…The performance-funding policy they examined also resulted in fewer minority students enrolled in public institutions subject to the policy. Similarly, Kelchen and Stedrak (2016) reported that at four-year institutions, Pell-Grant revenues per fulltime equivalent student (FTE) decreased under performance-funding programs, suggesting that institutions may have intentionally altered enrollment behaviors (by limiting access to lower income students) in response to performance funding.…”
Section: Previous Research On Performance-funding Policy Impactsmentioning
confidence: 99%
See 3 more Smart Citations
“…The performance-funding policy they examined also resulted in fewer minority students enrolled in public institutions subject to the policy. Similarly, Kelchen and Stedrak (2016) reported that at four-year institutions, Pell-Grant revenues per fulltime equivalent student (FTE) decreased under performance-funding programs, suggesting that institutions may have intentionally altered enrollment behaviors (by limiting access to lower income students) in response to performance funding.…”
Section: Previous Research On Performance-funding Policy Impactsmentioning
confidence: 99%
“…Further, the low-income measure does not extend to years prior to 1997. To examine the issue of measurement, we conducted a robustness check of these models using total Pell Grant revenue (ln) from IPEDS similar to the approach taken by Kelchen and Stedrak (2016). These models (not shown here)…”
Section: Premium Effects On Low-income Student Enrollmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…As of 2017, 35 states connect at least a portion of their higher education appropriations to PBF (Hillman, Fryar, & Crespín-Trujillo, 2018), with additional states, such as California, either considering or transitioning to a PBF policy (Fain, 2018). Gándara and Rutherford (2018) 1993-2014 Difference-in-difference Underserved student enrollment Yes Kelchen and Stedrak (2016) 2003-2012 Multivariate regression Institutional finances No Li (2018) 2003-2014 Difference-in-difference STEM bachelor's degrees Yes Merit aid Doyle (2010Doyle ( ) 1984Doyle ( -2005 Multivariate regression State merit aid per FTE No Fitzpatrick and Jones (2016) 1990-2010 Multivariate regression In-state and out-of-state attendance and residential migration Yes Kramer, Ortagus, and Lacy (2018) 1988 Difference-in-difference Tuition and fee levels Yes School accountability Hanushek and Raymond (2005) 1992 Multivariate regression Math and reading scores No Springer (2008) 2002 Note. STEM = science, technology, engineering, and mathematics; FTE = full-time equivalent.…”
Section: Case Study: Performance-based Funding In Higher Educationmentioning
confidence: 99%